Workplace Bullying in Higher Education Institutions - Aslanova, Khadija (ADA University, 2023)
Workplace Bullying gains an increasing interest as the world globalizes. Over the past decade, public and private organizations grew, and one can hear complaints, experiences, and sufferings employees share regarding workplace bullying. Accordingly, public universities as the type of organizations with CEOs, administrative staff, and technical workers are not the exception, and they may encounter workplace bullying. Thus, I decided to investigate workplace bullying in public universities. The focus of this study was to examine if workplace bullying existed in public universities and the types of workplace bullying that administrators and faculty members were exposed to. I, furthermore, strived to explore the effects of workplace bullying on the physical and emotional well-being of administrators and faculty members, as well as the quality of their services. The research employed a constructivist qualitative research design. Overall, six department heads and twelve faculty members were interviewed, and their perceptions and experiences related to workplace bullying were disclosed. The results of the study revealed that in that public university administrators and faculty members were aware of workplace bullying. Furthermore, the study uncovered several negative effects on both the physical and emotional well-being of academic administration and staff, and the quality of their services by creating physical illnesses, depression and self-inflicted injuries, and negligence and carelessness. The study also offered three strategies to handle workplace bullying, namely, solving the issue by discussing with the bully, turning the problem to authorities, and leaving the job based on answers of research participants to interview questions. The study adopted Maslow’s Hierarchy of Needs as a theoretical framework and participants’ perceptions and experiences were analyzed through three levels: Esteem, Social, and Safety. To prevent workplace bullying, respondents mentioned that there might be conferences, seminars, and special training dealing with workplace bullying in universities. Hence, I would recommend educational leaders and professionals rethink the policies and practices of public universities to maintain proactive behavior toward workplace bullying. Furthermore, launching special departments within each public university which may provide informative gatherings, healing sessions, and offer issue solutions may lead to the effective prevention method of workplace bullying and its consequences.
Keywords: Workplace bullying.; Bullying in universities.; Universities and colleges -- Employees -- Psychology; Public universities -- Administration; Education